Gifted Education in Chile: Analyses from a Learning-Resource Perspective - Gomez-Arizaga, M (Taylor and Francis Ltd., 2024)
This study aims to delve into the specific components of the Actiotope Model, which emphasizes the role of learning resources in education. It seeks to explore how these components are presented in the Chilean context of gifted education, while examining the current state of gifted education in the country. The methodology was a qualitative document analysis that included an active search for existing documents on gifted education and document analysis in the field of giftedness in Chile. The country owes a debt to the education of these students and urgently requires a broad vision of inclusion that truly addresses diversity and a legislation that makes them visible and establishes a framework to regulate their educational care. The findings of the study will contribute to a better understanding of the challenges and opportunities in gifted education in Chile and provide insights into how learning resources can be effectively utilized in this context. © 2024 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.